"Does Personality Matter? Exploring the Role of Diary Writing in Enhancing EFL Students’ Recount Writing Performance" - Faridha, Noor (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2025)
Writing is one of the most challenging skills for students learning English as a foreign language, especially in composing well-organized and meaningful texts such as recounts. Many students face difficulties in generating ideas, applying correct grammar, and expressing experiences coherently. This classroom-based activity was implemented at Al Falah Silo High School, Jember, in 2025 for 30 tenth-grade students to address these challenges. The main objective was to improve students' writing skills, particularly in writing recount texts, through the use of personal diary writing. The method used in this program was a process-based writing approach combined with reflective learning. During eight weekly sessions, students were guided to write diary entries recounting their personal experiences, following the structure of orientation, sequence of events, and reorientation. The teacher provided ongoing feedback and encouraged peer reflection to support the writing process. The results showed a significant improvement in students' ability to write coherent and well-structured recount paragraphs. Students also reported increased confidence, motivation, and enthusiasm in expressing their ideas through writing. This activity concludes that journaling can be an effective pedagogical tool for improving students' writing performance while fostering independence and self-expression in the context of English as a Foreign Language (EFL).